Titanium oxide-aluminum oxide compound and preparation method thereof
Through the combination of pH swing method and hydrothermal treatment, titanium oxide-alumina composites with high specific surface area and high pore distribution concentration were prepared, which solved the problem of insufficient performance of titanium oxide-alumina composites in the prior art and improved the The performance of the catalyst is suitable for industrial production.
Patent Information
- Application Number
- CN202310730263.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-24
AI Technical Summary
The specific surface area and pore volume of the existing titanium oxide-alumina composite are low, which cannot meet the performance requirements of the hydrogenation catalyst. The existing preparation methods have the problem of easy phase separation between alumina and titanium oxide.
Using a combination of pH swing method and hydrothermal treatment, the titanium oxide-alumina composite with a large specific surface area and a high pore distribution concentration was prepared, with a pore size of 6-10nm The holes account for more than 50% of the total holes.
It improves the resistance to carbon deposits, poisoning and acidic properties of the catalyst. It is suitable as a high-performance catalyst support material, and has a simple process and is suitable for large-scale industrial production.
Smart Images

Figure CN119175090A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of carrier materials and preparation thereof, and in particular relates to a titanium oxide-aluminum oxide composite and a preparation method thereof. Background Art
[0002] In order to protect the environment, countries around the world have formulated increasingly stringent environmental protection regulations and put forward higher quality requirements for petroleum products. The national standards have increasingly stringent requirements on the sulfur content and aromatic content in gasoline and diesel. Hydrogenation technology is one of the main ways to reduce sulfides and nitrides in fuel oil. The research and development of catalysts is the core of hydrogenation technology. The most commonly used carrier in hydrogenation catalysts is γ-alumina. In order to improve the performance of the catalyst to meet the needs of hydrogenation technology, other elements are usually added to alumina to prepare composite oxides. Through research, it is found that titanium oxide has good resistance to carbon deposition, anti-poisoning and good acidity. However, its own specific surface area and pore volume are small, and it is not suitable as a catalyst carrier material alone. If titanium oxide is compounded with alumina, the catalyst can have the advantages of high specific surface area, high pore volume, anti-coking and anti-poisoning.
[0003] Patent CN101199935A discloses a hydrodesulfurization catalyst with titanium-aluminum composite oxide as a carrier. The titanium-aluminum composite carrier is synthesized by a sol-gel method. The sols of titanium and aluminum are synthesized separately, and then mixed to form a carrier with a pore volume of 0.7-1.1 mL / g, a pore diameter of 9-14 nm, and a specific surface area of 230-350 m2 / g. Patent CN1429890A uses alumina to impregnate a titanium compound solution, then dry and calcine to obtain a titanium oxide-aluminum oxide composite with a specific surface of 80-180 m2 / g, a pore volume of 0.4-1.3 mL / g, and a maximum pore diameter of 9-15 nm. The specific surface area of the composites prepared by the above two methods is relatively low and needs to be further improved. Patent CN1098433A uses a kneading method to prepare titanium oxide-aluminum oxide. The disadvantage of this method is that alumina and titanium oxide are easily separated, which reduces the promoting effect of titanium oxide on the catalyst. Patent CN1273878A discloses a method for preparing a two-component titanium oxide-alumina oxide, which is prepared by co-precipitation of a mixture of a soluble titanium salt and a soluble aluminum salt with a sodium aluminate solution. The preparation method of the two-component mixture is simple, the raw materials are easily available, and the specific surface area is large. However, the pore volume of the two-component mixture is low and needs to be improved. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a titanium oxide-aluminum oxide composite with a large specific surface area and a highly concentrated pore distribution, and provides a method for preparing the material. Specifically, the present invention includes the following contents:
[0005] A titanium oxide-aluminum oxide composite, wherein the aluminum oxide content is 50%-99%, the titanium oxide content is 1%-50%, wherein the pore volume characterized by N2 adsorption and desorption is 0.50-1.60 mL / g, and the specific surface area is 250-550 m 2 / g, the most probable pore diameter is 4-12nm, and pores of 6-10nm account for more than 50% of the total pores.
[0006] The present invention provides a method for preparing a titanium oxide-aluminum oxide composite, comprising the following steps:
[0007] (1) preparing an acidic solution and an alkaline solution, wherein the acidic solution is an acidic aluminum-containing solution and an acidic titanium-containing solution, the acidic aluminum-containing solution is an aluminum sulfate solution and / or an aluminum nitrate solution and / or an aluminum chloride solution, the acidic titanium-containing solution is a solution formed by adding a titanium-containing compound to an acidic solution; the titanium-containing compound is one or more of titanyl sulfate, titanium trichloride, titanium tetrachloride, and titanium dioxide; the acidic solution is preferably an inorganic acid solution, and the inorganic acid can be one or more of sulfuric acid, nitric acid, and hydrochloric acid; the alkaline solution is an alkali metal solution and / or an alkaline aluminum-containing solution, the alkali metal solution is a sodium hydroxide solution, a potassium hydroxide solution, a sodium carbonate solution, or a potassium carbonate solution, and the alkaline aluminum-containing solution is a sodium aluminate solution and / or a potassium aluminate solution;
[0008] (2) adding a certain amount of water to the reactor, heating to the reaction temperature, and then alternately adding part of the acidic solution and part of any alkaline solution, adding the acidic aluminum-containing solution so that the pH value of the mixed system is 0.4-6.5, and adding the alkaline solution so that the pH value of the mixed system is 8.0-11.5; the acidic solution is added in 2-8 times;
[0009] (3) subjecting the mixed system obtained in step (2) to an aging treatment, wherein the treatment conditions include a temperature of 60 to 95° C. and a time of 0.5 to 8.0 hours;
[0010] (4) subjecting the mixed system obtained in step (3) to a hydrothermal treatment, wherein the treatment conditions include a temperature of 100-200° C. and a time of 0.5-12 hours;
[0011] (5) The solid product obtained by filtering the mixed system after the hydrothermal treatment is dried and calcined in sequence to obtain the titanium oxide-aluminum oxide composite.
[0012] Conventional supported hydroprocessing catalysts often have active centers distributed on the inner surface of the catalyst. Before being adsorbed, reactant molecules must diffuse through the pores of the catalyst to reach the active centers on the inner surface of the catalyst. This diffusion process is closely related to the pore structure of the catalyst, and therefore is also closely related to the structure of the carrier material. For residual oil hydrogenation reactions, according to the molecular structure characteristics and diffusion characteristics of the oil products, the pore distribution of the catalytic material is usually controlled at 6-10nm, and the higher the pore distribution ratio within this range, the higher the catalytic activity. Compared with the prior art, the titanium oxide-alumina composite described in the present invention has a larger specific surface area, pore volume and higher pore distribution concentration, and the pores of 6-10nm account for more than 50% of the total pores, and the interaction between titanium and alumina is stronger. The preparation method described in the present invention has a simple process, and the raw materials are cheap and easy to obtain, which is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the TEM image of the titanium oxide-aluminum oxide composite prepared in Example 1.
[0014] Figure 2 This is the TEM image of the titanium oxide-aluminum oxide composite prepared in Comparative Example 3.
[0015] Figure 3 This is the pore size distribution diagram of the titanium oxide-aluminum oxide composite prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. DETAILED DESCRIPTION
[0016] First of all, it should be noted that the endpoints and any values of the ranges disclosed in this specification are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0017] In a first aspect, the present invention provides a titanium oxide-aluminum oxide composite having specific pore characteristics, preferably, the aluminum oxide content is 55% to 97%, and the titanium oxide content is 3% to 45%; preferably, the pore volume characterized by BET is 0.50 to 1.30 mL / g, and the specific surface area is 300 to 530 m 2 / g, and the most probable pore size is 5 to 10nm. The titanium oxide-aluminum oxide composite of the present invention has a large specific surface area, pore volume and high pore distribution concentration, and the interaction between titanium and alumina is stronger. As a catalyst carrier material, it has good resistance to carbon deposition, anti-poisoning and good acidity, and can improve catalyst performance.
[0018] The N2 adsorption and desorption characterization method is as follows: N2 adsorption and desorption characterization is performed on a Micromeritics ASAP 2420 adsorption instrument. Before the test, about 0.3 g of titanium oxide-aluminum oxide composite powder is taken and pretreated at 350° C. and vacuum for 10 hours.
[0019] The contents of aluminum oxide and titanium oxide in the titanium oxide-aluminum oxide composite are expressed in mass percentages, wherein the specific determination method is as follows: after the sample powder is pressed into tablets, the characteristic spectral lines of each element are determined using a 3271 X-ray fluorescence spectrometer produced by Rigaku Corporation of Japan, and the content of each element is semi-quantitatively analyzed using an external standard method to obtain the composition of TiO2, Al2O3, etc. in the sample.
[0020] The TEM determination method is as follows: a trace amount of sample powder is placed on a copper grid and characterized using a Japanese Tecnai F20 G2 field emission transmission electron microscope (TEM).
[0021] In order to obtain the titanium oxide-aluminum oxide composite of the present invention, the present invention also provides a method for preparing the titanium oxide-aluminum oxide composite. The method mainly includes the steps of preparing a titanium oxide-aluminum oxide composite precursor and performing an aging treatment and a hydrothermal treatment on the precursor, wherein the precursor is prepared by a pH swing method, specifically, an acidic aluminum-containing component is added to the preparation system to reduce the pH to an acidic range of less than 7, and then an alkaline solution is added to the preparation system to increase the pH to an alkaline range of greater than 7, so that the pH of the preparation mixed system changes from a low acidic pH to a high alkaline pH or cycles between them. After the system has undergone one or more pH swings and the material addition is completed, the preparation mixed system is hydrothermally treated, and then filtered, dried, and roasted to obtain the titanium oxide-aluminum oxide composite of the present invention. The titanium oxide-aluminum oxide composite obtained using the method of the present invention has unique properties.
[0022] In a specific embodiment, the concentration of Al2O3 in the acidic aluminum-containing solution in step (1) is 50-120 g / L, the concentration of TiO2 in the acidic titanium-containing solution is 1-100 g / L, the concentration of the alkali metal solution is 1-100 g / L, and the concentration of Al2O3 in the alkaline aluminum-containing solution is 20-300 g / L.
[0023] In the step (2), an acidic aluminum-containing solution is added to adjust the mixed system to acidic, preferably with a pH value of 0.5-6, and an alkaline solution is added to adjust the mixed system to alkaline, preferably with a pH value of 8.5-11.0. When the acidic solution is added, only the acidic aluminum-containing solution or the acidic titanium-containing solution can be added, or the acidic aluminum-containing solution and the acidic titanium-containing solution can be added at the same time, or the compounds containing aluminum and titanium can be configured together to form an acidic solution, and the acidic solution contains both aluminum-containing substances and titanium-containing substances.
[0024] According to the method of the present invention, the pH swing can have multiple cycles. Generally, the first step is to add an acidic aluminum-containing solution or an acidic titanium-containing solution, and the last step is to add an alkaline solution, preferably 3-6 cycles; further preferably, the acidic aluminum-containing solution is added in 2 to 6 times, and the acidic titanium-containing solution is added in 1 to 6 times.
[0025] If a fixed amount of solution is prepared, after the last addition of the acidic solution, all the remaining alkaline solution is added, and the pH value of the system after the last addition of the acidic solution and the alkaline solution is not subject to the above restrictions.
[0026] The reaction conditions during the pH swing process are conventional gelling reaction conditions. Generally, the reaction temperature is 25-90° C.; preferably, the reaction is carried out under stirring at a stirring speed of 100-1000 rpm.
[0027] According to the present invention, the aging treatment and hydrothermal treatment in steps (2) and (3) can improve the pore structure of the carrier. The inventors of the present invention have found that the combination of pH swing method and hydrothermal method can not only increase the pore volume and the pore diameter, but also the pore distribution concentration of the titanium oxide-aluminum oxide composite is higher, which is very suitable for use as a catalyst carrier. Under preferred conditions, the hydrothermal treatment conditions in step (3) are a temperature of 110-180°C and a time of 2-10 hours.
[0028] The pH swing preparation of titanium oxide-aluminum oxide composite precursor and aging and hydrothermal treatment of the present invention can be carried out in a single reactor, such as in a reactor, with a simple reaction process and small equipment investment; the raw materials are easily available, no template is required, the overall process is environmentally friendly, and is very suitable for industrial production.
[0029] The present invention will be further explained below through specific preferred embodiments, but it should be noted that the present invention is not limited by the conditions of the embodiments.
[0030] Example 1
[0031] In this embodiment, the aluminum sulfate solution has a concentration of 104 g / L in terms of Al2O3, a free acid concentration of 3 gH2SO4 / L, and a Fe2O3 concentration of ≤150 mg / L; the sodium aluminate has a concentration of 220 g / L in terms of Al2O3, and a Na2O concentration of 227 g / L. 30 g of titanyl sulfate (TiOSO4·xH2SO4·xH2O) is dissolved in 50 mL of aluminum sulfate solution. During the preparation process, 300 mL of water is first added to the reactor and heated to 55°C. Then, solutions of titanyl sulfate, sodium aluminate, aluminum sulfate, sodium aluminate, etc. are added in the order of Table 1. The pH of the liquid after each step of operation is also listed in Table 1. After each dropwise addition, stir for 5 min at a stirring speed of 600 rpm. After the addition is completed, the solution is aged at 90°C for 4 h, and the liquid is transferred to a high-pressure reactor with a hydrothermal temperature of 140°C and a hydrothermal time of 4 hours. After the hydrothermal step, the sample was filtered, washed, dried at 120 °C for 12 hours, and calcined at 600 °C for 3 hours to obtain a titanium oxide-aluminum oxide composite. The TEM image is shown in Figure 1 As shown, the hole distribution diagram is as follows Figure 3 The physicochemical properties are shown in Table 4.
[0032] Table 1
[0033]
[0034]
[0035] Comparative Example 1
[0036] The process of the pH swing preparation part (step 1 to step 9) of Comparative Example 1 is completely consistent with that of Example 1. The obtained mixed solution is aged at 90° C. for 4 hours, and then directly filtered, washed, dried and calcined. The drying and calcining conditions are the same as those of Example 1. The pore distribution diagram of the titanium oxide-aluminum oxide composite prepared in Comparative Example 1 is shown in FIG. Figure 3 The physicochemical properties are shown in Table 4.
[0037] Comparative Example 2
[0038] Comparative Example 2 has the same raw material concentration and addition amount as Example 1, but does not form gel through the pH swing method. During the preparation process, first add 300 mL of water into the reactor and heat it to 55°C. Then add aluminum sulfate, titanyl sulfate, and sodium aluminate solution to the reaction vessel at the same time. After the addition is completed, continue stirring for 10 minutes at a stirring speed of 600 rpm. The solution is then aged at 90°C for 4 hours. After the aging step is completed, the sample is filtered, washed, dried at 120°C for 12 hours, and calcined at 600°C for 3 hours to obtain a titanium oxide-aluminum oxide composite. The pore distribution diagram of the titanium oxide-aluminum oxide composite is shown in Figure 3 The physicochemical properties are shown in Table 4.
[0039] Comparative Example 3
[0040] The raw material concentration and addition amount of Comparative Example 3 are consistent with those of Example 1, but the gelation is not performed through the pH swing method. During the preparation process, 300 mL of water is first added to the reactor and heated to 55°C. Then, aluminum sulfate, titanyl sulfate, and sodium aluminate solution are added to the reaction vessel at the same time, and stirring is continued for 10 minutes after the addition is completed. The solution is then aged at 90°C for 4 hours. After the aging step is completed, the liquid is transferred to a high-pressure reactor, the hydrothermal temperature is 140°C, and the hydrothermal time is 4 hours. After the hydrothermal process is completed, the sample is filtered, washed, dried at 120°C for 12 hours, and calcined at 600°C for 3 hours to obtain a titanium oxide-aluminum oxide composite. The TEM image of the titanium oxide-aluminum oxide composite is shown as follows Figure 2 As shown, the hole distribution diagram is as follows Figure 3 The physicochemical properties are shown in Table 4.
[0041] Example 2
[0042] In this embodiment, the aluminum sulfate solution has a concentration of 104 g / L in terms of Al2O3, a free acid concentration of 3 gH2SO4 / L, and a Fe2O3 concentration of ≤150 mg / L; the sodium aluminate has a concentration of 220 g / L in terms of Al2O3, and a Na2O concentration of 227 g / L. 10 g of titanyl sulfate (TiOSO4·xH2SO4·xH2O) is dissolved in 50 mL of aluminum sulfate solution. During the preparation process, 200 mL of water is first added to the reactor and heated to 55°C. Then, titanyl sulfate, sodium aluminate, aluminum sulfate, and sodium aluminate are added in the order of Table 2. The pH of the liquid after each step of operation is also listed in Table 2. After each dropwise addition, stir for 5 minutes at a stirring speed of 600 rpm. After the addition is completed, age at 95°C for 3 hours. After aging, transfer to a high-pressure reactor with a hydrothermal temperature of 150°C and a hydrothermal time of 3 hours. After the hydrothermal step, the sample was filtered, washed, dried at 120°C for 12 hours, and calcined at 600°C for 3 hours. The physicochemical properties of the titanium oxide-aluminum oxide composite are shown in Table 4.
[0043] Table 2
[0044] step Components Liquid pH after addition 1 Deionized water 7.2 2 Titanyl sulfate 0.83 3 Sodium aluminate 10.0 4 Aluminum sulfate 3.0 5 Sodium aluminate 9.7 6 Aluminum sulfate 3.5 7 Sodium aluminate 8.9 8 Aluminum sulfate 3.3 9 Sodium aluminate 10.4
[0045] Example 3
[0046] In this embodiment, the concentration of aluminum sulfate solution is 80g / L in terms of Al2O3; the concentration of sodium aluminate is 180g / L in terms of Al2O3, and the concentration of Na2O is 160g / L. 30g of titanyl sulfate (TiOSO4·xH2SO4·xH2O) is dissolved in 50mL of aluminum sulfate solution. During the preparation process, 1000mL of water is first added to the reactor and heated to 40°C. Then, aluminum sulfate, sodium aluminate, titanyl sulfate, and sodium aluminate are added in the order of Table 3. The pH of the liquid after each step is also listed in Table 3. After each dropwise addition, stir for 5min at a stirring speed of 400rpm. After the addition is completed, age at 85°C for 5h, transfer to a high-pressure reactor, and the hydrothermal temperature is 130°C for 5 hours. After the hydrothermal step is completed, the sample is filtered, washed, dried at 120°C for 12 hours, and calcined at 550°C for 3 hours to obtain a titanium oxide-alumina composite. The physicochemical properties of the titanium oxide-aluminum oxide composite are shown in Table 4.
[0047] Table 3
[0048] step Components Liquid pH after addition 1 Deionized water 6.9 2 Aluminum sulfate 3.7 3 Sodium aluminate 9.2 4 Titanyl sulfate 1.2 5 Sodium aluminate 9.5 6 Aluminum sulfate 3.0 7 Sodium aluminate 9.7
[0049] Table 4
[0050]
Claims
1. A titanium oxide-aluminum oxide composite, wherein the aluminum oxide content is 50%-99% and the titanium oxide content is 1%-50%, wherein: The pore volume characterized by N2 adsorption and desorption is 0.50-1.60 mL / g, and the specific surface area is 250-550 m 2 / g, the most probable pore diameter is 4-12nm, and pores of 6-10nm account for more than 50% of the total pores.
2. The titanium oxide-aluminum oxide composite according to claim 1, wherein The aluminum oxide content is 55% to 97%, and the titanium oxide content is 3% to 45%.
3. The titanium oxide-aluminum oxide composite according to claim 1, wherein The pore volume characterized by N2 adsorption and desorption is 0.50-1.30 mL / g, and the specific surface area is 300-530 m 2 / g, the most probable pore diameter is 5-10nm, and pores of 6-10nm account for more than 55% of the total pores.
4. The method for preparing the titanium oxide-aluminum oxide composite according to claim 1, comprising the following steps: (1) preparing an acidic solution and an alkaline solution, wherein the acidic solution is an acidic aluminum-containing solution or an acidic titanium-containing solution, the acidic aluminum-containing solution is an aluminum sulfate solution and / or an aluminum nitrate solution and / or an aluminum chloride solution, the acidic titanium-containing solution is a solution formed by adding a titanium-containing compound to an acidic solution, the alkaline solution is an alkali metal solution and / or an alkaline aluminum-containing solution, the alkali metal solution is a sodium hydroxide solution, a potassium hydroxide solution, a sodium carbonate solution or a potassium carbonate solution, and the alkaline aluminum-containing solution is a sodium aluminate solution and / or a potassium aluminate solution; (2) adding a certain amount of water to the reactor, heating to the reaction temperature, and then alternately adding part of the acidic solution and part of any alkaline solution, adding the acidic aluminum-containing solution so that the pH value of the mixed system is 0.4-6.5, and adding the alkaline solution so that the pH value of the mixed system is 8.0-11.5; the acidic solution is added in 2-8 times; (3) subjecting the mixed system obtained in step (2) to an aging treatment, wherein the treatment conditions include a temperature of 60 to 95° C. and a time of 0.5 to 8.0 hours; (4) subjecting the mixed system obtained in step (3) to a hydrothermal treatment, wherein the treatment conditions include a temperature of 100-200° C. and a time of 0.5-12 hours; (5) The solid product obtained by filtering the mixed system after the hydrothermal treatment is dried and calcined in sequence to obtain the titanium oxide-aluminum oxide composite.
5. The method according to claim 4, wherein: In step (1), the concentration of Al2O3 in the acidic aluminum-containing solution is 50-120 g / L, the concentration of TiO2 in the acidic titanium-containing solution is 1-100 g / L, the concentration of the alkali metal solution is 1-100 g / L, and the concentration of Al2O3 in the alkaline aluminum-containing solution is 20-300 g / L.
6. The method according to claim 4, wherein: In the step (2), an acidic solution is added to make the pH value of the mixed system 0.5-6, and an alkaline solution is added to make the pH value of the mixed system 8.5-11.
0.
7. The method according to claim 4, wherein: In the step of adding the acidic solution in step (2), an acidic titanium-containing solution and / or an acidic aluminum-containing solution may be added. The acidic aluminum-containing solution may be added in 2 to 6 portions, and the acidic titanium-containing solution may be added in 1 to 6 portions.
8. The method according to claim 4, wherein: The reaction temperature of step (2) is 25-90° C.; preferably, step (2) is carried out at a stirring speed of 100-1000 rpm.
9. The method according to claim 4, wherein: The step (2) is carried out at a stirring speed of 100-1000 rpm.
10. The method according to claim 4, wherein: The drying conditions in step (5) include: temperature 100-180° C., time 6-24 hours; the roasting conditions are: temperature 400-800° C., time 0.5-12 hours.
